Impact of immediately loaded implant-supported maxillary full-arch dental prostheses: a systematic review - Ahlam ABDUNABI; Martin MORRIS; Samer Abi NADER; Raphael F. de SOUZA (Journal of Applied Oral Science)
Abstract The immediate loading of implant-assisted fixed prostheses in edentulous maxillae may achieve favorable success rates with reduced treatment time. An evidence summary of clinical trials is key to recommend loading protocols in these cases. Objectives To compare immediately loaded, fully implant-supported complete dentures to early and conventional/delayed loading in the edentulous maxillae of adult patients by a systematic review of controlled clinical trials (CCT). Methodology CCTs reports were identified up to January 17, 2019 from Cochrane Oral Health Group’s Trial register, Cochrane Central Register of controlled trials (CENTRAL), MEDLINE (Ovid), BIOSIS, EMBASE, CINAHL, Web of Science, and DARE. Two independent reviewers screened titles/abstracts and confirmed inclusion using full texts. Data were extracted and quality assessed (Cochrane Risk of Bias tool) independently and in duplicate. Study heterogeneity prevented pooling by meta-analysis. Results Out of 1,052 candidate studies, four CCTs were included. Two trials had patient satisfaction as an outcome: (1) A randomized trial compared immediately and early loaded fixed dentures and found more satisfaction with the first after 12 months; (2) A non-randomized study found better satisfaction with immediate fixed dentures compared to conventional loading after 3 months (no more at 12 months). Regarding implant success and prosthetic complications, three trials did not report significant differences comparing immediate loading to other protocols. Conclusions This review found weak evidence of differences between immediate load and other loading regimens, regarding patient satisfaction and maintenance events/adversities. The potential of immediate loading for favorable results in edentulous maxillae reinforces the need for well-designed RCTs, for solid clinical guidelines. Registration number CRD42018071316 (PROSPERO database).